Mapping Green Financial Management Research Trends with a Global Bibliometric Study - Judijanto, Loso; Qosim, Nanang; Regar, Erfendi; Arifin, Hasmia Melati; Faisal, Muhammad (Eastasouth Institute, 2025)
This bibliometric study analyzes the dynamic landscape of green finance research from 2000 to 2023, revealing the evolution of key themes, geographic and collaboration patterns, and shifts in research focus over time. Utilizing data from Scopus and VOSviewer, the study highlights significant growth in publications, particularly post-2015, aligned with increased global attention towards sustainable development. The research maps out central themes including